2023
DOI: 10.3390/jcm12124063
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Inappropriate Medications Use among Older Adults with Dyslipidaemia

Abstract: Background: Since older patients with dyslipidemia frequently receive many prescriptions, medication errors are typical and expected in this population. This risk has increased by using potentially inappropriate medications. The 2019 Beers criteria were used in this study to investigate potentially inappropriate medication use among older individuals with dyslipidemia. Methods: A cross-sectional retrospective analysis used data from electronic medical records from an ambulatory-care environment. Patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A systematic review and metaanalysis showed a global prevalence of PIM use of 36.7% [8], which is lower than that found in this study (58.5%). However, other studies show prevalence rates closer to those found [9,10]. A study carried out in Portugal showed that 79.7% of elderly people admitted to an internal medicine service used at least one PIM [11].…”
Section: Discussionmentioning
confidence: 89%
“…A systematic review and metaanalysis showed a global prevalence of PIM use of 36.7% [8], which is lower than that found in this study (58.5%). However, other studies show prevalence rates closer to those found [9,10]. A study carried out in Portugal showed that 79.7% of elderly people admitted to an internal medicine service used at least one PIM [11].…”
Section: Discussionmentioning
confidence: 89%
“…This may be explained by older patients being predisposed to comorbid conditions, leading to polypharmacy and exposure to medication side effects, thus resulting in inadequate statin intensification. 40 …”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by older patients being predisposed to comorbid conditions, leading to polypharmacy and exposure to medication side effects, thus resulting in inadequate statin intensification. 40 In addition to the gaps related to indications for and dose intensification of statins, the shortage of other lipid-lowering agents in low-income countries has significant consequences. Important lipid lowering agents such as ezetimibe and proprotein convertase subtilisin/kexin type 9 (PCSK9) were not available in the study setting.…”
Section: Dovepressmentioning
confidence: 99%